ANALISIS HUKUM TERHADAP HAK-HAK REHABILITASI BAGI PENYALAHGUNA NARKOTIKA DI INDONESIA - Kasimin (2020)
This study aims to identify and explain the criminal proof system for rehabilitation rights for narcotics abusers based on positive law in Indonesia. And to find out and explain the factors causing the disparity in judge decisions between rehabilitation decisions and imprisonment for narcotics abusers in Indonesia. The theory used is the theory of proof of crime and the theory of rehabilitation. The research method used is a juridical analysis method with a qualitative approach. The results of the research, based on the formulation of Article 183 KUHAP, the judge to determine whether a defendant is legal or not and to be able to pass a sentence on a defendant must have two conditions, namely: two valid pieces of evidence, the judge must have confidence that the defendant was guilty of doing so. Every criminal action must have a sanction which is proven in the trial process and there must be a judge's decision. In deciding criminal narcotics related to the abuse of narcotics Category I instead of plants, the judge is obliged to provide medical and social rehabilitation. The discretion held by the judge to decide crimes related to narcotics abuse in Article 127 jo Article 103 of the Narcotics Law. The factor in the disparity in judges' decisions is due to the use of various terms for a subject who uses narcotics which have implications for the reporting mechanism and rehabilitation measures and the impact of the crime. In addition, because of that the assessment encountered obstacles and one of them was the difference in views of law enforcers in addressing the status of addicts in the Narcotics case. On the one hand there is the phrase "not proven guilty", but on the other hand there is the phrase "ordered" which is a statement explaining the existence of an error and in the form of a punishment for the accused. The conclusion is that in relation to rehabilitation rights in narcotics crime as stipulated in the provisions of Article 103 of Law Number 35 of 2009 concerning Narcotics, judges are given the authority to examine and decide cases of narcotics abuse undergoing treatment and / or treatment as a period of serving a sentence. for narcotics addicts. The disparity in the judge's decision in the case of narcotics abusers can be seen in the evidence of the indictment filed by the public prosecutor which is based on Article 103 of the Narcotics Law in the form of a judge's decision to impose a length of time serving a sentence by granting rehabilitation rights for narcotics abusers. Referring to Article 184 of the Criminal Procedure Code, where evidence using forensic laboratory results is the basis that strengthens the evidence as evidence of guidance, evidence of letters and expert statements